Survey of Trees and Shrubs Used for Amenity Purposes in Ekiti State - Olujobi; John, Olagunju (International Journal For Research In Agricultural And Food Science, 2016)
Amenity uses of landscape trees to mankind in terms of provision of healthy environment and other aesthetic values are sometimes greater than the monetary value of their marketable wood. This study assesses the diversity and distribution of trees used for amenity purposes in Ekiti State. A total of one hundred and sixty pre-tested questionnaires were randomly administered to respondents for collection of data. Results obtained revealed that Thirty one (31) different trees/shrubs are planted for amenity purposes in the study area with Ficus thonningii having the highest percentage of occurrence (10.51 %). These trees are mostly planted in schools (18.96 %), hospitals (17.63 %) and markets (16.91 %,) by the respondents across the study area to provide various economic, socio-cultural and environmental benefits. Considering the important role been played by these urban trees/shrubs in environmental amelioration, government should enact laws mandating estate developers to plant trees in their compound for urban greening.